DIFFERENCES IN PSYCHOLOGICAL WELL-BEING OF ADOLESCENTS REVIEWED BY EDUCATIONAL FACTORS: A COMPARATIVE STUDY BETWEEN MARGINALIZED AND CENTRALIZED GROUPS IN INDONESIA - Andini Dwi Arumsari; Amirul Haq Al Amin; Takdir Auladi; Maulana Andarru Bayu Saputra; Moch Nabiel Makariem (P3I UMSurabaya, 2025)
This study aims to compare the psychological well-being of Indonesian adolescents in terms of educational factors, specifically between marginalized and centralized groups. Using a qualitative approach with a literature review design (Snyder, 2019), this study analyzed 35 scientific publications and institutional reports. The synthesis results indicate that unequal access and quality of education creates gaps in the fulfillment of basic psychological needs (autonomy, competence, relatedness) (Ryan & Deci, 2000) and widens the gap in cultural capital (Bourdieu, 2011). Centralized adolescents demonstrate more stable well-being, excelling in the dimensions of autonomy and personal growth, supported by adaptive learning environments (Asih et al., 2024). Meanwhile, marginalized adolescents exhibit fluctuating well-being, weak in self-acceptance and environmental mastery (Fazny et al., 2022). The resilience of marginalized groups is more defensive and community-based (collective coping), rather than psychological growth (flourishing). This study concludes that education functions as an important psychosocial mechanism that determines the psychological development of adolescents, so that inclusive education policies that are sensitive to psychological aspects are needed to create psychological justice.